Karakteristik Konten TikTok Merek Lokal untuk Generasi Z di Indonesia: Analisis Isi Kualitatif - Andhini Winariyanti; Ridha Handayani; Juni Alfiah Chusjairi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines TikTok content as a platform-native communication artifact shaped by brand strategy, platform logic, and Generation Z preferences. It adapts Munsch’s (2021) audience-perception model by shifting the analytical focus from audience responses to observable brand-generated content construction. Using qualitative content analysis supported by descriptive statistics, this study analyzes 69 TikTok posts, consisting of 64 videos and 5 photo/carousel posts from three Indonesian local brands, namely Somethinc, Scarlett Whitening, and Erigo, published from 1 to 15 May 2026. Seven communication elements were coded by two independent coders: compact format, viral music, humor, figure/creator/KOL presence, authenticity, informative message, and call-to-action. Intercoder reliability was strong across the six variable elements, with average Cohen’s Kappa and Krippendorff’s Alpha scores of 0.95. The analysis identifies three dominant content configurations: science-led educational content, figur/KOL-mediated community intimacy, and figur/KOL-led trend conversion. Humor emerges as the most strategic differentiator, supported by visual evidence from selected screenshots. The findings suggest that, within the observed corpus, the three brands do not rely on a single viral content formula. Instead, Indonesian local brands navigate algorithmic visibility through category-specific content construction.